Characterization of PTEN gene as a prognostic biomarker in prostate cancer - Albuquerque, Clarissa Gondim Picanço de (2017)
The PTEN tumor suppressor gene is a promising biomarker for prostate cancer with strong biological evidence that its loss of function will be associated with aggressive disease. This thesis was designed to identify the association between PTEN loss and the clinical outcome in homogeneous Gleason score 7 prostate cancer cohorts from Brazil and the USA for improved stratification of the use of loss of PTEN as an indicator of poor prognosis. In addition, ongoing correlative studies are showing an association between PTEN loss and altered T-cell infiltration in the tumor-tissue microenvironment (TME). From the Brazilian cohort, we performed a correlative evaluation of PTEN loss from 43 patients undergoing radical prostatectomy through Fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC). From the USA, we evaluated two cohorts: an in silico analysis of 244 radical prostatectomy tumors obtained from The Cancer Genome Atlas (TCGA), and a case control cohort of 111 needle biopsies from the Johns Hopkins Medical School. The analysis of the case controls showed that PTEN loss by FISH and IHC was predictive of the upgrade to in radical prostatectomy. Collectively, these studies sindicate that the frequency of PTEN loss the cohort studies, using FISH, IHC and in an in silico analysis of array-CGH were similar (~20%). By FISH and IHC in the Brazilian cohort, we observed a significant association between PTEN loss and worse prognosis and a trend for the occurrence of earlier biochemical recurrence. In the copy number landscape of the Gleason 7 patients from the TCGA cohort, we observed concomitant alterations in the genome of patients that harbored PTEN homozygous or hemizygous deletions. For this in silico analysis, we found that PTEN gene deletion is associated with the extraprostatic extension (P-value = 0.05) and with disease recurrence (P-value = 0.03). We also observed that PTEN deletion events may occur with more frequency in white men (P-value = 0.01) when compared to Asians and African American men. By IHC, we evaluated the rate of CD8+ T-cell infiltration in the TME of the prostate cancer samples from the Brazil cohort. CD8+ T-cell showed a trend to a significant increased CD8+ TIL infiltration in samples that harbored PTEN homozygous deletions. In this thesis, PTEN gene has been characterized as an informative biomarker for prostate cancer stratification and outcome prediction due to its functionality and impact in cell proliferation and also appearing to have an emerging role as a biomarker of immune response in the tumortissue microenvironment.